Effect of Oral PUVAsol on the Quality of Life in Indian Patients Having Chronic Plaque Psoriasis - Pratik Gahalaut; Nitin Mishra; Puneet S. Soodan; Madhur K. Rastogi (Hindawi Limited, 2014)
Background. Psoriasis is associated with a high impact on health-related QoL (quality of life). PUVAsol has been successfully used for treating psoriasis instead of standard PUVA therapy in developing countries. However, data for PUVAsol therapy and its effect on QoL in psoriatic patients is meagre. Objective. To investigate the effect of PUVAsol on the quality of life in patients having chronic plaque psoriasis. Materials and Methods. An observational prospective study done in patients having chronic plaque psoriasis. PASI and DLQI were calculated before initiating treatment with oral PUVAsol. These were compared with the respective scores after 12 weeks of regular treatment with PUVAsol. Statistical analysis was done using SPSS version 20.0. Results. Both PASI and DLQI showed statistically significant reduction after 12 weeks of regular treatment. 90% of patients responded favourably to PUVAsol therapy in the study and all the domains of DLQI showed significant reduction except domain of "work and school." Conclusion. Our results show that regular PUVAsol treatment improves the physical appearance of disease as evident by decrease in PASI scores. It also improves the QoL of the patients. This study will add upon the growing evidence of efficacy of PUVAsol.